The Effect of Liquid Smoke on the Quality of Uncooked Smoked Sausages - Dashtoyan, A. L.; Balayan, E. B.; Mirzabekyan, S. A. (ՀԱԱՀ հիմնադրամ)
Meat products are highly nutritious, shelf stable and widely consumed food products. Today, a wide range of meat products is produced in the Republic of Armenia, which differ from each other in terms of quantity and variety of raw materials, additives, heat treatment, as well as in storage and packaging conditions. The aim of the scientific work is to reveal the threats caused upon the use of different smoking methods in the production of uncooked smoked sausages in the meat industry and to study their quality indicators.
Keywords: Food Science and Technology